Gestión administrativa y su incidencia en la calidad de servicios de la empresa Agrimen Quevedo, año 2023 - Chóez Holguín, Génesis Annabell (2025)
The main objective of this research was to analyze administrative management and its impact on service quality at Agrimen Company, located in the Quevedo canton, in the year 2023. The study was conducted using a mixed-methods approach, combining both qualitative and quantitative methodologies, and was classified as descriptive, field-based, bibliographic, and documentary research. Deductive, inductive, and statistical methods were applied throughout the process. The target population consisted of the company's clients, with a representative sample of 196 surveys. In addition, an interview was conducted with the company’s representative. The research findings revealed that 40% of clients perceived the company’s responsiveness positively, and 39% had a favorable view of its tangibility. However, only 24% expressed a positive perception of reliability, while dimensions such as empathy and security showed high levels of neutrality. Consequently, the most critical areas identified were reliability, empathy, and security, which negatively impact overall service perception. It was concluded that, although technical strengths exist within the staff and tangible conditions are favorable, an administrative transformation is required—one that prioritizes standardized protocols, strengthens the human component, and enhances communication—to optimize the customer experience.